Evaluation of relationship generated between concrete fiber properties and permeability - Mudhafar Shawka AL-obaidi, Abdullha (International Journal of Advanced Engineering, Management and Science, 2022)
The research aims to Evaluation of a relationship generated between concrete fiber properties and permeability. All concrete samples were examined in Baghdad, Iraq, where 8 samples for beams were collected distributed on cutting and flexural tests, and 16 samples were collected for the cylinder distributed on compression and tensile strength tests. The study found that fibrous concrete reduces permeability and thus reduces water bleeding, as some types of fibers produce greater impact and resistance to abrasion and fracture in concrete. In general, fibers do not increase the flexural strength of concrete, so they cannot replace structural or resistive rebar, some fibers reduce the strength of concrete. This can be explained from the general concept of the mechanism of action of the fibers inside the manufactured concrete, which, when exposed to stresses, works to form connecting bridges through the internal cracks in the concrete, which may contribute to creating additional resistance after the cracks occur.